Survival of 86, 690 patients with thyroid cancer: A population-based study in 29 European countries from EUROCARE-5. (May 2017) - Dal Maso, L.; Tavilla, A.; Pacini, F.; Serraino, D.; van Dijk, B.A.C.; Chirlaque, M.D.; Capocaccia, R.; Larrañaga, N.; Colonna, M.; Agius, D.; Ardanaz, E.; Rubió-Casadevall, J.; et al.
Abstract: Background: Incidence rates of thyroid cancer (TC) increased in several countries during the last 30 years, while mortality rates remained unchanged, raising important questions for treatment and follow-up of TC patients. This study updates population-based estimates of relative survival (RS) after TC diagnosis in Europe by sex, country, age, period and histology. Methods: Data from 87 cancer registries in 29 countries were extracted from the EUROCARE-5 dataset. One- and 5-year RS were estimated using the cohort approach for 86, 690 adult TC patients diagnosed in 2000–2007 and followed-up to 12/31/2008. RS trends in 1999–2007 and 10-year RS in 2005–2007 were estimated using the period approach. Results: In Europe 2000–2007, 5-year RS after TC was 88% in women and 81% in men. Survival rates varied by country and were strongly correlated (Pearson ρ = 75%) with country-specific incidence rates. Five-year RS decreased with age (in women from >95% at age 15–54 to 57% at age 75+), from 98% in women and 94% in men with papillary TC to 14% in women and 12% in men with anaplastic TC. Proportion of papillary TC varied by country and increased over time, while survival rates were similar across areas and periods. In 1999–2007, 5-year RS increased by five percentage points for all TCs but only by two for papillary and by four for follicular TC. Ten-year RS in 2005–2007 was 89% in women and 79% in men. Conclusions: The reported increasing TC survival trend and differences by area are mainly explained by the varying histological case-mix of cases. Highlights: This is the largest population-based study on the topic (86, 690 cases). In Europe (2000–2007), 5-year RS after thyroid cancer was 88% in women and 81% in men. A gap of 10 percentage points emerged across European areas. A strong correlation (ρ = 75%) between survival and incidence rates emerged by country. Survival variations by area and period are mainly explained by varying case-mix.